Adaptable Techniques for Making IT-Related Investment Decisions - Peter Sasvari (International Journal of Advanced Research in Computer Science and Software Engineering, 2012)
The author investigated the main methods used for making IT-related investment decisions. In the view of these methods it can be said that no method was found that would help to make investment decisions 'routinelike'. The use of traditional financial indicators – which would be suitable for so-called regular investments - has a lot of obstructions and it would be dangerous to base decisions only on them. Return on Investment (ROI) methods are used in the case of classical investments (buildings, machineries) to analyze capital investments. Their simplest explanation is that net profit is expressed in percentage of invested capital. If it is a planned investment, a quotient is used for comparing variations. Cost-Benefit Analysis (CBA) has gained upon from the 60's (in case of several IT-related investments as well), as it made possible to consider certain not quantifiable factors and uncertain elements too, so it meant a great help for choosing between different alternatives. Total Cost of Ownership (TCO)-model was created by GartnerGroup in the beginning of the 90's, which is an excellent method for monitoring IT infrastructure and for analysing direct and indirect costs of possessed and used softwares and hardwares. An another method for making investment decisions, Rapid Economic Justification (REJ) is an attempt made by Microsoft and Intellectual Arbitrage to develop a better-balanced approach for examining and developing IT projects as it had been before. REJ offers the possibility of assessment balance against the cost-models dealing with only the cost side of a project.
Keywords: M15; M13; 330; Return on Investment; Cost-Benefit Analysis; IT investment; Rapid Economic Justification